YOUTH, RELIGION, AND POP CULTURE: MODERNITAS DALAM GAYA HIDUP HEDONISME REMAJA DAN BUDAYA POPULER VERSUS EKSISTENSI AGAMA JAMAN NOW - Soleh, Muhammad Soleh (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This research discusses the role of modernity in influencing the hedonistic lifestyle of teenagers and popular culture's impact on the existence of religion in the present time. Contemporary society is often confronted with cultural and value changes brought about by technological advancements and globalization. In this context, teenagers face complex challenges in navigating between the demands of popular culture that support pleasure and hedonism, and the more traditional values and teachings of religion. This study adopts a qualitative approach with interview techniques and observational data collection to understand teenagers' perceptions and experiences regarding religion and popular culture. The findings indicate that popular culture, such as social media, music, and entertainment, tends to promote a hedonistic lifestyle that emphasizes instant gratification and material pleasure. Meanwhile, religious values often appear marginalized and lose relevance for some teenagers. However, the research also discovered that some teenagers still hold onto their religious beliefs and try to integrate religious values with existing popular culture. Some religious groups also make efforts to leverage social media and other forms of popular culture as tools to spread religious teachings and maintain their presence in the modern world. In conclusion, teenagers in the present time face a conflict between the hedonistic lifestyle and the existence of religion, which can influence how they perceive and practice religion. It is essential for society and religious leaders to understand these dynamics and seek relevant and inclusive ways to interact with the younger generation so that religious values can remain relevant and beneficial in shaping the character and ethics of today's teenagers.